THE ROLE OF THE LOCAL GOVERNMENT IN ASSISTING AND FOSTERING ADHERENTS OF THE "JOURNEY" BELIEF STREAM OF CIPARAY BANDUNG REGENCY - Adiwilaga, Rendy; Puji, Gentra (Journal of Social Politics and Governance (JSPG), 2024)
Ethnic and cultural diversity in Indonesia is an important foundation for tolerance, including in the diversity of religions and beliefs. One of the schools of belief recognized in Indonesia is the "Journey" school, whose existence is guaranteed by law and receives assistance and guidance in accordance with Permendikbud No. 77 of 2013. This study aims to analyze the role of the Bandung Regency Regional Government in carrying out assistance and coaching for adherents of the "Travel" belief stream in Ciparay. Using qualitative research methods and narrative approaches, data were obtained through in-depth interviews with relevant agencies in the Bandung Regency Regional Government and representatives of believers. The results of the study show that assistance efforts by the Regional Government are still limited, only including supervision and socialization regarding the rights of believers to the community. Until now, there has been no concrete cooperation or comprehensive coaching steps, due to the absence of regional regulations that specifically regulate the assistance and development of believers. This finding emphasizes the need for local regulations that support the implementation of coaching more optimally, so that the rights of believers can be guaranteed and their existence is more recognized in society.